Aristotle on memory and recollection : text, translation, interpretation, and reception in Western scholasticism - Bloch, David, 1975- (Philosophia antiqua,, 2007)
Twentieth-century Scholarship on Aristotle's De Memoria et Reminiscentia was dominated by the view that Aristotle's theories of memory and recollection are basically very similar to ours. By means of a new critical edition of the Greek text, an essay on Aristotle's own theories and an essay on these theories as they were received in the Latin West, the present book offers material that challenges the opinio communis. The result is a new interpretation of Aristotle's De Memoria et Reminiscentia and its relevance to the concerns of 21st-century philosophers, both regarding the concepts of memory and recollection and regarding Aristotle's philosophical methodology.